2013
DOI: 10.1590/s1516-89132013005000018
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent RNA interference to increase isoflavone biosynthesis in soybean (Glycine max)

Abstract: In this work, a bivalent RNA interference (RNAi) plant-transformation vector was constructed to silence both the flavanone 3-hydroxylase (F3H) gene and the flavone synthase II (GmFNSII) gene in soybean (Glycine max). Two further unit RNAi vectors were constructed for each of these two genes. RNAi-mediated suppression of these genes effectively regulated flavone and isoflavone production in hairy roots that arose from soybean cotyledons transformed with Agrobacterium rhizogenes ATCC15834. Notably, the bivalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In another study, overexpression of CHS6 and IFS2 genes resulted in the reduced level of isoflavones and increased level of phenolic compounds ( Lozovaya et al, 2007 ). Jiang et al (2010 ; 2014 ) explored the negative regulation of F3H and GmFNSII genes by the RNAi-mediated gene silencing studies. Previously, the gene silencing of GmFNSII resulted in the increased accumulation of genistein in soybean hairy roots ( Jiang et al, 2010 ).…”
Section: Regulation Of Isoflavone Production Through Genetic Engineering In Soybeanmentioning
confidence: 99%
“…In another study, overexpression of CHS6 and IFS2 genes resulted in the reduced level of isoflavones and increased level of phenolic compounds ( Lozovaya et al, 2007 ). Jiang et al (2010 ; 2014 ) explored the negative regulation of F3H and GmFNSII genes by the RNAi-mediated gene silencing studies. Previously, the gene silencing of GmFNSII resulted in the increased accumulation of genistein in soybean hairy roots ( Jiang et al, 2010 ).…”
Section: Regulation Of Isoflavone Production Through Genetic Engineering In Soybeanmentioning
confidence: 99%
“…These metabolites are known to exhibit anticancerous and anti-osteoporotic activities in animal systems. Jiang et al (2014) enhanced isoflavone production in soybean hairy roots by down-regulating two flavonoid genes, the F3H and the flavones synthase II ′′ . In tobacco, Pandey et al (2014) showed a substantial amount of genistein glycoconjugates as a result of the co-expression of the transcription factor AtMYB12 with the soybean IFS gene”.…”
Section: Engineering Of Flavonoid Pathwaymentioning
confidence: 99%
“…The coexpression of Arabidopsis AtMYB12 and Lotus japonicus LjIFS in tomato f3h mutant also led to enhanced biosynthesis of isoflavones (Zhang et al , ). When GmF3H‐1 and GmFNSII‐2 were silenced separately or simultaneously in soya bean hairy roots by RNAi, the isoflavone content was strongly increased (Jiang et al , ; Jiang et al , ).…”
Section: Introductionmentioning
confidence: 99%